UMP researcher received CRDF2 grant of RM 1.06 million - Arun, Gupta (2021)
KUANTAN, 13 September 2021 - Professor. Dr. Arun Gupta from Faculty of Chemical and Process Engineering Technology, UMP received CRDF2 funding of RM 1.06 million from Malaysian Technology Development Corporation (MTDC) for the commercialization of Bioactive keratin protein.